2015
DOI: 10.1002/jctb.4632
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanisms of adsorption/desorption of the ionic liquid 1‐buthyl‐3‐methylimidazolium bromide into mordenite

Abstract: BACKGROUND Kinetics of adsorption and desorption associated with diffusion mechanisms is of crucial importance to use zeolites as catalysts. In particular, diffusion of ionic liquids (IL) is of interest when using them as solvent for reactions or preparing composite IL–Zeolite. This work investigated the kinetics of adsorption/desorption of 1‐buthyl‐3‐methylimidazolium bromide ([BMIM]+Br−) into mordenite (MOR), a channel‐like zeolite. RESULTS The adsorbed IL is characterized and quantified using infrared spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…All of these works [41,42,43,44,45,46,47,48,49,50] concluded that K2 better described the experimental kinetic data, except in ref. [49] in which K1 gave a better fit in the case of As(V) adsorption (while K2 was more satisfactory in the case of Cr(III) and Cr(VI)).…”
Section: Data Reported In 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…All of these works [41,42,43,44,45,46,47,48,49,50] concluded that K2 better described the experimental kinetic data, except in ref. [49] in which K1 gave a better fit in the case of As(V) adsorption (while K2 was more satisfactory in the case of Cr(III) and Cr(VI)).…”
Section: Data Reported In 2015mentioning
confidence: 99%
“…Among these publications 4 could not be used because all of the data were at equilibrium [41,42,43,44]. As a consequence, these studies unsurprisingly reported better performance of K2 over K1 as noted in section 3.1.…”
Section: Data Reported In 2015mentioning
confidence: 99%
“…ILs have been implemented in a wide range of industrial applications, including fuel cells [85], solar cells [86], batteries [87], and sensors [127] due to their unique properties such as low volatility, non-flammability, high thermal stability, and high ionic conductivity [128][129][130][131][132]. ILs are liquids comprised completely of ions from salts, which have a melting point below 100 • C. There are many sub-categories of ILs, including room temperature ILs, task-specific ILs, polyionic liquids, and supported IL membranes [131].…”
Section: Ionic Liquid (Il) Conjugated Echsmentioning
confidence: 99%
“…These models are the most commonly used to describe the sorption of dyes. They include all steps of adsorption such as external film diffusion, adsorption, and internal particle diffusion (Chanie et al 2015).…”
Section: Kinetics Studymentioning
confidence: 99%